PENGARUH PEMBIAYAAN SYARIAH TERHADAP RETURN ON ASSET (ROA) DENGAN NON-PERFORMING FINANCING (NPF) SEBAGAI VARIABEL MODERASI PADA BANK UMUM SYARIAH PERIODE 2018-2022 - Putri Nadia Sarly; Rayyan Firdaus; Yunina Yunina (Jurnal Akuntansi Malikussaleh (JAM), 2025)
Abstract This study aims to examine the effect of sharia financing on Return on Assets (ROA) with Non-Performing Financing (NPF) as a moderation variable in Islamic commercial banks in Indonesia for the 2018-2022 period. The population in this study includes all Islamic commercial banks registered with the Indonesian Financial Services Authority (OJK), with samples taken through the purposive sampling method based on certain criteria. This study uses panel data and is analyzed using the panel regression method to test the influence of independent variables of mudharabah, musharakah, and murabahah financing on the dependent variable of ROA, with NPF as the moderation variable. The results of the study show that mudharabah and musharakah financing have a significant influence on ROA, while murabahah financing has no significant effect. NPF as a moderation variable strengthens the influence of mudharabah and musharakah financing on ROA, but does not have a significant effect on murabahah financing. This research is expected to contribute to the development of financing strategies in Islamic commercial banks to increase profitability and risk management efficiency.